2023
DOI: 10.1186/s40364-023-00452-1
|View full text |Cite
|
Sign up to set email alerts
|

The function and clinical implication of YTHDF1 in the human system development and cancer

Abstract: YTHDF1 is a well-characterized m6A reader protein that is essential for protein translation, stem cell self-renewal, and embryonic development. YTHDF1 regulates target gene expression by diverse molecular mechanisms, such as promoting protein translation or modulating the stability of mRNA. The cellular levels of YTHDF1 are precisely regulated by a complicated transcriptional, post-transcriptional, and post-translational network. Very solid evidence supports the pivotal role of YTHDF1 in embryonic development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 101 publications
1
7
0
Order By: Relevance
“…RNA pull-down and RIP assays demonstrated that YTHDF1, but not the other readers, could bind to PSEN1 mRNA. YTHDF1 is an important m 6 A modification reader, and its primary function is to promote protein translation or regulate the stability of m 6 A-modified mRNAs [ 49 , 50 ]. Notably, YTHDF1 knockdown attenuated ameliorated pulmonary artery smooth muscle cell proliferation, phenotypic switching, and the development of pulmonary hypertension by enhancing MAGED1 translation both in vivo and in vitro [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…RNA pull-down and RIP assays demonstrated that YTHDF1, but not the other readers, could bind to PSEN1 mRNA. YTHDF1 is an important m 6 A modification reader, and its primary function is to promote protein translation or regulate the stability of m 6 A-modified mRNAs [ 49 , 50 ]. Notably, YTHDF1 knockdown attenuated ameliorated pulmonary artery smooth muscle cell proliferation, phenotypic switching, and the development of pulmonary hypertension by enhancing MAGED1 translation both in vivo and in vitro [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…It participates in several crucial physiological or pathological processes, such as cell proliferation, embryonic development, tumorigenesis, and neurogenesis [ 49 – 52 ]. RNA modification is a reversible process dynamically coordinated by a series of catalytically active methyltransferases, demethylases, and methylation-recognition proteins [ 53 55 ]. Taking the particularly well-investigated m6A methylation process as an example, adenylate methylation is performed by the methyltransferase complex.…”
Section: Introductionmentioning
confidence: 99%
“…The m6A is catalyzed by a multicomponent protein complex including methyltransferases (METTL3, METTL14, and KIAA1429), demethylases (FTO and ALKBH5), and m6A‐binding proteins (YTHDF1‐3, YTHDC1, and YTHDC2) 8 . Studies have found that the upregulation of YTHDF1 promotes tumorigenesis and metastasis, which is related to poor prognosis of various tumors 9,10 . In addition, the upregulation of YTHDF1 promotes the stemness features and chemotherapy resistance of tumor cells 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…8 Studies have found that the upregulation of YTHDF1 promotes tumorigenesis and metastasis, which is related to poor prognosis of various tumors. 9,10 In addition, the upregulation of YTHDF1 promotes the stemness features and chemotherapy resistance of tumor cells. 11,12 However, the role of YTHDF1 in TNBC is currently unclear.…”
Section: Introductionmentioning
confidence: 99%